2018
DOI: 10.14368/jdras.2018.34.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a self - applied paint - on whitening gel combined with wrap

Abstract: The aim of this clinical study was to evaluate the efficacy and safety of a self-applied paint-on whitening gel combined with wrap to increase the effect of a whitening gel and minimize gingival irritation. Materials and Methods: Ninety adult volunteers were randomly treated to a control group and two experimental groups using whitening gel containing 2.8% and 3.0% hydrogen peroxide for 30 persons each. They had used the wrap and whitening gel on maxillary 4 anterior teeth for 30 minutes per day during 2 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies by Kim et al 7) and Ahn et al 22) found that tooth whitening with teeth whitening gels and toothpaste was effective. In this study, we also observed an increase in the lightness of specimens following the use of tooth whitening gel and toothpaste.…”
Section: Key Results and Comparison With The Results Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Kim et al 7) and Ahn et al 22) found that tooth whitening with teeth whitening gels and toothpaste was effective. In this study, we also observed an increase in the lightness of specimens following the use of tooth whitening gel and toothpaste.…”
Section: Key Results and Comparison With The Results Of Previous Studiesmentioning
confidence: 99%
“…At-home whitening is performed using individual trays with 10% to 15% hydrogen peroxide. Finally, OTC whitening products with low concentration that can be easily purchased online are available for at-home use 7) . Furthermore, the interest in tooth whitening among modern-day individuals extend beyond teeth whitening procedures to everyday oral care products, such as toothpaste and mouthwash, which have added whitening functions.…”
Section: Introductionmentioning
confidence: 99%
“…The reason why the color change values were greater than the standards put forth by Gross and Moser 26) in the two studies may be attributed to the fact that the specimen used had undergone an artificial tooth surface staining process. For instance, in a previous study by Kim et al 11) , where the bleaching process took place without previous staining, the average color change was △E * ab= 3.40, but in the case of another study by Kim et al 16) that used specimens that had undergone a staining process, a greater color change of △E * ab=34.02 was detected.…”
Section: Comparison Of Surface Damagementioning
confidence: 93%
“…In fact, side effects such as change in the enamel and hypersalivation have been reported. Kim et al 11) have also reported that even commercially available low-concentration home bleaching agents can cause side effects such as hypersensitivity, burns, and damage to hard dental tissue if applied for longer than the recommended.…”
Section: Introductionmentioning
confidence: 99%